1989
DOI: 10.1530/jrf.0.0860195
|View full text |Cite
|
Sign up to set email alerts
|

Circulating progesterone concentrations and ovarian functional anatomy in the African elephant (Loxodonta africana)

Abstract: Summary. Mean

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…Postmortems on culled, pregnant African elephants showed that all CLs are equally capable of producing P m (Hodges et al 1997). We were unable to determine a correlation between CL number, size, and peripheral P m which agreed with an earlier study (De Villiers et al 1989).…”
Section: Luteogenesis In Elephantscontrasting
confidence: 75%
See 1 more Smart Citation
“…Postmortems on culled, pregnant African elephants showed that all CLs are equally capable of producing P m (Hodges et al 1997). We were unable to determine a correlation between CL number, size, and peripheral P m which agreed with an earlier study (De Villiers et al 1989).…”
Section: Luteogenesis In Elephantscontrasting
confidence: 75%
“…The mean number of CLs in cycling elephants is not different from pregnant elephants and progestagen concentrations do not increase over consecutive cycles (De Villiers et al 1989, Hodges et al 1997. These findings led Hodges (1998) to disagree with the theory of CL accumulation.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, maternal blood progesterone concentrations are at about 7 ng/ml between 50 and 100 days of gestation (Echternkamp et al 2006), which is lower than the 20-150 ng/g progesterone concentration seen in fetal ovaries between 60 and 75 days of gestation. Previous literature has established that maternal and fetal progesterone levels are different from each other and may be regulated independently in macaques (Ducsay et al 1985, Thau et al 1976), humans (Donaldson et al 1991), sheep (Nicol et al 1997) and elephants (de Villiers et al 1989). This suggests that ovarian fetal progesterone is regulated to control the initiation or progression of primordial follicle assembly, independent of maternal progesterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Given that prolactin is luteotropic in other mammals, the increase after 20-28 weeks could account for some of the progestagen activity observed later in pregnancy. The lack of a correlation between circulating progestagen levels and luteal volume [de Villiers et al, 1989], and the positive relationship between fetal progestagen concentrations and gestational age [de Villiers et al, 1989] both suggest that the placenta may be a source of progestagens.…”
Section: Discussionmentioning
confidence: 99%